Emerging advances in nanobiomaterials-assisted chimeric antigen receptor (CAR)-macrophages for tumor immunotherapy - Zhang, Yanan; Yang, Jingxing; Zhang, Tinghao; Gu, Hongchen (Frontiers in Bioengineering and Biotechnology, 2023)
Adoptive cell immunotherapy, especially chimeric antigen receptor (CAR)-T cells therapy, has made great progress in the clinical treatment of hematological malignancies. However, restricted by the complex tumor microenvironment, the potential efficiency of T cell infiltration and activated immune cells are limited, thus failure prevented the progression of the solid tumor. Alternatively, tumor-associated macrophages (TAMs), one sustentacular and heterogeneous cellular population within the tumor microenvironment, are regarded as potential therapeutic targets. Recently, CARs have shown tremendous promise in treating malignancies by equipping macrophages. This novel therapeutic strategy circumvents the tumor microenvironment's limitations and provides a safer therapeutic approach. Meanwhile, nanobiomaterials as gene delivery carriers not only substantially reduce the treatment cost of this novel therapeutic strategy, but also set the foundation for in vivo CAR-M therapy. Here, we highlight the major strategies prepared for CAR-M, emphasizing the challenges and opportunities of these approaches. First, the common therapeutic strategies for macrophages are summarized in clinical and preclinical trials. Namely, TAM-targeted therapeutic strategies: 1) inhibit monocyte or macrophage recruitment into tumors, 2) deplete TAMs, and 3) reprogramme TAMs to antitumor M1 phenotype. Second, the current development and progress of CAR-M therapy are reviewed, including the researchers' attempts in CAR structure design, cell origin, and gene delivery vectors, especially nanobiomaterials as an alternative to viral vectors, as well as some challenges faced by current CAR-M therapy are also summarized and discussed. Finally, the field of genetically engineered macrophages integration with nanotechnology for the future in oncology has been prospected.